Chiari type I malformation with cervicothoracic syringomyelia subterfuge as flail arm syndrome - Zhi Gang Lan; Seidu A. Richard; Jiagang Liu; Chao You (MDPI AG, 2017)
Chiari type I malformation with cervicothoracic syringomyelia although very common in clinical practice usually in children can progress slowly and mimic muscular dystrophies in adulthood. We present a rare adult case of Chiari type I malformation with cervicothoracic syringomyelia subterfuge as Flail arm syndrome. A 44- year-old man was diagnosed with congenital type I Chiari malformation with cervicothoracic syringomyelia about 21 years ago without surgery. His health status deteriorated over the years until 21 days prior to presentation when he had severe pain in the right knee. In his upper limbs, he had bilateral corresponding severe weakness of 0/5 proximal strength and 0/5 strength in his distal muscles. Magnetic resonance imaging (MRI) revealed an enlargement of the spinal cord from C1-C4 level with a mass that appeared hypo-dense on T1 and hyperdense on T2. Syringomyelia is a potentially serious neurologic condition that can mimic other neuromuscular disorders. Early detection and diagnosis with MRI is crucial to avoid irreversible neurological complications. We suggest that whether asymptomatic or symptomatic, decompressive surgery should be carried out to allow for free flow of cerebrospinal fluid thereby improving the quality of life for the patient.